Trade, Insecurity, and the Costs of Conflict - Michelle R. Garfinkel; Stergios Skaperdas; Constantinos Syropoulos (Center for Economic Studies and ifo Institute (CESifo), 2022)
Typically, economics assumes that property rights over productive resources or goods are perfectly defined and costlessly enforced. The costs of insecurity and the resultant conflict are, however, real and often economically significant. In this paper, we examine how international trade regimes affect the costs of conflict and, in turn, how the desirability of international trade is affected by these costs. We consider both domestic and international conflict. Trade openness reduces the costs of these types of conflict for countries that import goods whose production relies on supplies of contested resources. For countries that export such goods, trade openness intensifies conflict. The effect of conflict on the allocation of productive resources through prices under trade can also explain the "natural resource curse" and can overturn a country's natural comparative advantage. Finally, we consider alternative channels through which trade can affect arming and conflict costs, with effects that can either improve or worsen international relations.
Keywords: C72; C78; D30; D70; D74; F10; F51; F60; 330; insecure resources; trade openness; the gains from trade; domestic conflict; interstate conflict